Temporomandibular dysfunction : detection of signs and symptoms in patients of the Egas Moniz university clinic - Domun, Lina Khan (2025)
Aim: In patients who attended the Triage Consultation in the Clinic of the Egas Moniz University Clinic in 2023, evaluate the presence of signs and symptoms associated with TMD. And the relationship between these data and those obtained in the Occlusion Consultation. Materials and methods: The clinical records of 1425 patients who attended the Triage Consultation at the Egas Moniz University Clinic during 2023, aged between 18 and 45 years, were analysed. Data were collected regarding the reason for the consultation and the presence of signs and symptoms associated with TMD. Subsequently, information from the Occlusion Consultation was gathered. The collected data were organised and subjected to statistical analysis. Results: A significant association was found between the presence of signs and symptoms and the factors gender, purpose of consultation, and attendance at the Occlusion Consultation. Almost one-third of the patients (32%) exhibited at least one sign or symptom of TMD, with women (68.8%) representing the majority of affected individuals. Among symptomatic patients, only 3% reported TMJ pain as their reason for consultation. The most frequent signs were TMJ click (24%), followed by TMJ pain (10.7%), bruxism (5.9%), and limited mandibular movements (5.5%). Despite detection during the Triage Consultation, only 13.5% of these 32% of patients proceeded to the Occlusion Consultation for further evaluation. Conclusion: This study confirmed that TMD is a common condition, especially among women. However, many patients did not attend a specialised consultation for a more accurate TMD diagnosis and appropriate treatment, revealing a gap between detection and management. Better patient education, clearer communication, and a standardised referral system are essential to ensure the timely treatment of TMD.